2007
DOI: 10.1590/s1413-99362007000100005
|View full text |Cite
|
Sign up to set email alerts
|

Indicadores bibliométricos de cooperação científica internacional em bioprospecção

Abstract: Busca observar os fatores que influem nas relações de colaboração científica de uma atividade de pesquisa multidisciplinar - a área de bioprospecção - como afinidades econômicas, culturais e geográficas. Apresenta e analisa indicadores bibliométricos de co-autoria que abrangem o período de 1986 a 2006, computados a partir de uma base bibliográfica internacional e multidisciplinar, o Science Citation Index.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
8

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 5 publications
0
7
0
8
Order By: Relevance
“…In studies of Latin American biodiversity, nations tend to seek partners with technical-scientific knowledge and financial resources (usually from North America) to aid in the exploration of their biodiversity [21]. …”
Section: Resultsmentioning
confidence: 99%
“…In studies of Latin American biodiversity, nations tend to seek partners with technical-scientific knowledge and financial resources (usually from North America) to aid in the exploration of their biodiversity [21]. …”
Section: Resultsmentioning
confidence: 99%
“…The existence of a cluster between São Paulo and Paraná state universities was observed in articles published between 1986 and 2006 in the area of Bioprospecting [19]. The same study showed EMBRAPA and the federal universities of Lavras and Viçosa to appear isolated in the cluster analysis.…”
Section: Results Presentation and Analysismentioning
confidence: 75%
“…A negociação entre os pesquisadores sobre quem vai assinar determinado artigo, além de variar entre as áreas, reflete o contexto histórico e social em que se localizam os colaboradores (LIMA; VELHO;FARIA, 2007). Nas palavras de Luukkonen, Persson e Sivertsen (1992, p. 103, tradução nossa):…”
Section: Definição De Colaboração Científicaunclassified